Management Survival Skills: Managing as a Non Librarian in an Academic Library - Moore, Rhonda; Pearce, Ann (My University, 2017)
Presentation at the OLA Superconference on managing in an academic library. Taken from the point of view of non librarians, the presentation focused on skill sets needed, training, experience, lessons learned, etc.
Keywords: Management; Academic Library; Library Technician; Management Skills